Providing Gender Responsive Work Facilities To Support Women's Empowerment And Child Protection - Agustanti, Rosalia Dika; Sugiyono, Heru; Herbawani, Chahya Kharin; Samodro, Dewanto (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
This research uses normative juridical methods. The research technique begins by sorting the laws and regulations governing Gender, and this is done to find out how available work facilities are in the Depok City Government. PPPA Ministerial Regulation No. 5 of 2015 concerning Providing Gender Responsive Work Facilities and Caring for Children in the Workplace, the aim is to fulfil the right to protection for women and children; Fulfillment of children's rights and guarantee children's growth and development; Environmental responsibility in the care and protection of children; Increase work productivity. The unavailability of lactation rooms, the availability of special waiting rooms for children in the workplace, and the implementation of curfews for female workers are the main focus, and this certainly supports SDS5, namely Gender Equality. Thus, workplaces must provide facilities and infrastructure that take into account the principles of gender equality and the best interests of children. The provision of gender-responsive facilities and infrastructure is intended to increase work productivity and pay attention to the best interests and growth and development processes of children. Apart from fulfilling and protecting the rights of women and children, this includes fulfilling the rights and protection of people with disabilities and the elderly. The result is that the Depok City Government has not yet demonstrated work facilities that have a gender perspective. Therefore, to accelerate this fulfilment, the Government should be able to utilize old, habitable buildings to fulfil work facilities with a gender perspective.